Drought Monitoring Using MOWCATL Data Mining Algorithm in Aras Basin, Turkey - Topcu, Emre (Earth sciences research journal, 2022)
Drought is a natural phenomenon that occurs frequently and has some adverse effects on the ecosystem and humanity. Determination of drought beforehand is vital for optimal management of water resources. Many different methods have been developed to detect drought. Sequential association analysis is used for the data series analysis containing time information and is one of the methods used to determine the drought. A correlation can be established between the values taken by the data at different times when determining association rules with this method. The primary purpose of this study is to determine the sequential association patterns between precipitation and climate oscillation index for Aras Basin. The Aras basin is a region where irrigation and animal husbandry are common. Today many dams and hydroelectric power plants, together with the increasing population, meet the water and energy needs. A possible drought event in this region will adversely affect the living things in the basin. Therefore, the study focused on this basin. Finding sequential associations between precipitation and climate oscillation index can determine the temporal correlations between these parameters and specifically detect drought. The MOWCATL (Minimal Occurrences with Constraints and Time Lags) algorithm was used to detect sequential associations, and the J-measure was used to evaluate the patterns in the study. Sequential association patterns were determined by applying this method to the precipitation data obtained from 6 meteorology stations in the Aras basin. AO (Arctic Oscillation) Index, MEI (Multivariate ENSO) Index, NAO (North Atlantic Oscillation) Index, Oceanic Nino Index (ONI), PDO (Pacific Decadal Oscillation) Index, PNA (Pacific/North American), and SOI (Southern Oscillation Index), followed by the 1, 3, 6 and 12-month Agricultural Standardized Precipitation Index (a-SPI) were used in sequential association. The study results revealed that the antecedent parameters were ineffective in detecting arid conditions in Ardahan and Dogubeyazit stations, and they were influential on drought conditions, especially in a-SPI-3 and a-SPI-12 month periods at other stations. Although the altitude and geographical features are different, similar climatic patterns have been detected in some stations. As a result, it has been determined that climatic oscillations generally bring about typical situations in terms of drought for the Aras Basin. Keywords: data mining drought index; drought; oceanic index Monitoreo de la sequia a traves del algoritmo MOWCATL de mineria de datos para la cuenca de Aras, Turquia La sequia es un fenomeno natural que ocurre muy frecuentemente y que tiene efectos negativos en los ecosistemas y en la humanidad. La definicion de la sequia, de antemano, es especialmente necesarua para la administracion optima de los recursos de agua. Muchos metodos se han desarrollado para detectar la sequia. Uno de estos metodos es el analisis de asociacion secuencial que se usa para el analisis de series de datos con informacion de tiempo. Se puede establecer una correlacion entre los valores tornados en diferentes periodos cuando se determinan las reglas asociativas con este metodo. El proposito principal de este estudio es determinar los patrones de asociacion secuencial entre precipitacion y el indice de oscilacion climatica para la cuenca de Aras, en Turquia. Esta cuenca es una region donde la irrigacion y la agricultura son comunes. Al dia de hoy, muchas presas e hidroelectricas, junto con el incremento de la poblacion, demandan estos recursos hidrologicos. Un evento de sequia en la region afectaria a estos seres que dependen de la cuenca. Por esta razon, el estudio se enfoca en la cuenca de Aras. Encontrar las asociaciones secuenciales entre precipitacion y el indice de oscilacion climatica puede determinar las correlaciones temporales entre estos parametros y especificamente, detectar la sequia. En este trabajo se uso el algoritmo MOWCATL (ocurrencias minimas con restricciones y retrasos, literal del ingles Minimal Occurrences with Constraints and Time Lags) para detectar las asociaciones secuenciales y la medicion J se uso para evaluar estos patrones. Los patrones de asociacion secuencial se determinaron al aplicar este metodo a la informacion de precipitacion obtenida de seis estaciones meteorologicas en la cuenca de Basin. Los indices de Oscilacion Artica, ENSO Multivariado, Oscilacion del Atlantico Norte, Oceanico del Nino, Oscilacion Decadal del Pacifico, Pacifico/Norte America, y de Oscilacion del Sur, seguidos por el Indice de Precipitacion Agricola Estandarizado (a-SPI) en los meses 1,3,6 y 12 se utlizaron en la asociacion secuencial. Los resultados del estudio revelan que estos parametros no son efectivos para detectar las condiciones aridas en las estaciones de Ardahan y Dogubeyazit pero si son efectivos en las condiciones de sequia, especialmente en los periodos a-SPI-3 y a-SPI-12 en otras estaciones. A pesar de que las condiciones de altitud y geograficas son diferetes, patrones climaticos se han detectado en algunas estaciones. Como resultado se determino que las oscilaciones climaticas generalemente provocan situaciones normales de sequia en la cuenca de Aras. Palabras clave: mineria de datos; indice de sequia; sequia; indice oceanico.